2019
DOI: 10.1002/slct.201900714
|View full text |Cite|
|
Sign up to set email alerts
|

Size‐controlled Cobalt Ferrite Nanocrystals: Magnetically separable Reusable Nanocatalysts for Selective Oxidation of Styrene

Abstract: Superparamagnetic cobalt ferrite (CFO) nanocrystals (NCs) with sizes ∼ 6 nm and ∼ 4 nm were synthesized using a facile solvothermal method using fatty acids, lauric acid and stearic acid, as the capping agents. The synthesized nanocrystals were well characterized by XRD, FT-IR, XPS, SEM and TEM. The formation mechanism was explored and it was shown that the fatty acid was actually chemisorbed as a carboxylate onto the surface of CFO NCs. The experimental results specify that the size and size distribution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 79 publications
2
23
0
Order By: Relevance
“…The peak located at 532.5 eV can be attributed to chemisorbed oxygen species. 36 The peak at 530.1 eV is attributable to lattice oxygen (i.e., Fe-O) in the CFO. However, the broad complex O 1s peak of the TA-CFO NPs could be deconvoluted into three peaks, which also contains peaks for lattice oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak located at 532.5 eV can be attributed to chemisorbed oxygen species. 36 The peak at 530.1 eV is attributable to lattice oxygen (i.e., Fe-O) in the CFO. However, the broad complex O 1s peak of the TA-CFO NPs could be deconvoluted into three peaks, which also contains peaks for lattice oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…The peak located at 532.5 eV can be attributed to chemisorbed oxygen species. 36 The peak at 530.1 eV is attributable to lattice oxygen ( i.e. , Fe–O) in the CFO.…”
Section: Resultsmentioning
confidence: 99%
“…Particle size control is very important for the photocatalysis process. In the literature, it is reported that NPs of controlled size showed high catalytic activity such as Fe 3 O 4 , in addition to being an effective catalyst material for the degradation of organic pollutants . Fe 3 O 4 NPs have also been used as the solid support for the development of magnetically recoverable catalytic systems .…”
Section: Resultsmentioning
confidence: 99%
“…12−14 Inspired by the above facts, here we have synthesized metal ferrite (MFO), M 2+ Fe 2 O 4 (M 2+ = Mn, Co, Ni, and Zn) NCs with a controlled size of ∼4 nm by a facile solvothermal method using stearic acid as the stabilizing agent via a similar protocol published earlier from our group. 15 The OER electrocatalytic performance of the ∼4 nm MFO NCs, [MnFe 2 O 4 (MnFO), CoFe 2 O 4 (CoFO), NiFe 2 O 4 (NiFO), and ZnFe 2 O 4 (ZnFO)] was examined in a 1 M KOH aqueous electrolyte using carbon paper (CP) and nickel foam (NF) as substrates. The as-synthesized MnFO, CoFO, NiFO, and ZnFO NCs exhibited distinct OER activity in different substrates, e.g., CP and NF.…”
Section: ■ Introductionmentioning
confidence: 99%